From Stimulus to Consolidation : Revenue and Expenditure Policies in Advanced and Emerging Economies. (Policy Papers; Policy Paper, 2010)
This review marks the 10th anniversary of the safeguards policy. Introduced in March 2000, the policy's main objective is to mitigate potential risks of misuse of resources, including Fund resources, and misreporting of monetary program data. The policy was last reviewed in 2005, when the Executive Board re-affirmed the effectiveness of the policy, and its application to central banks. In keeping with previous reviews, a panel of experts was invited to provide advice for the Executive Board on the implementation of the policy, and recommendations to guide the focus and application of the policy going forward.